Confronting Myths: How Violence in Ciudad Juarez Affects El Paso, Texas - Prose, Rob Daniel (URJ-UCCS: Undergraduate Research Journal at UCCS, 2013)
This is a field-study looking at the effects of Ciudad Juarez drug cartel violence and its affects on the city of El Paso, Texas. This study examines criminal, economical, and societal effects of the drug wars that have encapsulated this region.